2013
DOI: 10.1017/s109285291300059x
|View full text |Cite
|
Sign up to set email alerts
|

D2receptor occupancy following lurasidone treatment in patients with schizophrenia or schizoaffective disorder

Abstract: Positron emission tomography (PET) occupancy data suggest that greater than 65% occupancy can be achieved across the dose range of 80-160 mg/day and that some patients require higher doses to achieve antipsychotic efficacy; this finding supports prior randomized clinical trial results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…schizophrenia randomly assigned to receive lurasidone 80, 120, or 160 mg/d for 1 week indicated that doses greater than 80 mg/d may be necessary to achieve therapeutic threshold levels of D 2 receptor occupancy in some patients. 28 In support of these observations, in this study, serum lurasidone concentration increased in a dose-related fashion, with an approximately 2-fold increase observed in patients treated with lurasidone 160 mg/d compared with patients continued on 80 mg/d. Notably, serum lurasidone concentration in patients receiving lurasidone 80 mg/d did not differentiate treatment responders from nonresponders at week 2.…”
Section: B Cgi-s Score Dsupporting
confidence: 80%
See 1 more Smart Citation
“…schizophrenia randomly assigned to receive lurasidone 80, 120, or 160 mg/d for 1 week indicated that doses greater than 80 mg/d may be necessary to achieve therapeutic threshold levels of D 2 receptor occupancy in some patients. 28 In support of these observations, in this study, serum lurasidone concentration increased in a dose-related fashion, with an approximately 2-fold increase observed in patients treated with lurasidone 160 mg/d compared with patients continued on 80 mg/d. Notably, serum lurasidone concentration in patients receiving lurasidone 80 mg/d did not differentiate treatment responders from nonresponders at week 2.…”
Section: B Cgi-s Score Dsupporting
confidence: 80%
“…Imaging studies have shown a strong relationship between serum lurasidone concentration and D 2 receptor occupancy. 27,28 A PET study of patients with It is illegal to post this copyrighted PDF on any website. schizophrenia randomly assigned to receive lurasidone 80, 120, or 160 mg/d for 1 week indicated that doses greater than 80 mg/d may be necessary to achieve therapeutic threshold levels of D 2 receptor occupancy in some patients.…”
Section: B Cgi-s Score Dmentioning
confidence: 99%
“…Among the five dopamine receptor subtypes, DRD2 seems to be the cardinal type that regulate the firing rate, synthesis and release of dopamine in presynaptic membrane [18]. Signal transduction through DRD2 controls substance abuse, locomotor behavior and antipsychiatric drug treatment response in ADHD patients [19][20][21]. Thus, it is not unexpected that rs1800497 variance is associated with the occurrence of ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…127 Another PET investigation of lurasidone in a large group of schizophrenia patients, however, showed that daily doses only modestly correlate with receptor occupancies, which were, however, predicted by plasma levels of the compound, along with its active metabolites. 128 It is well-known in therapeutic drug monitoring (TDM) that daily doses may fail to reliably predict plasma levels, clinical response, or side effects. 129 PET investigations, however, also uncovered that some agents, notably the AP quetiapine, fail to even reveal plasma concentration vs occupancy relationships, which calls into question the validity of simple daily dose suggestions for this compound.…”
Section: ■ Pet In Clinical Drug Development Using the Example Of Antimentioning
confidence: 99%